Entrepreneurship and Growth An International Historical Perspective - Tortella, Gabriel; Quiroga, Gloria; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
A collection of eight articles by 17 specialists, this volume provides very recent research on the factors which contribute to the build up of entrepreneurship. Offers an international, comparative and historical perspective, with a special focus upon the Mediterranean.
Keywords: International business enterprises; Management; Small business; Leadership; Organization; Planning; New business enterprises; International Business; Management; Small Business; Business Strategy/Leadership.; Organization; Start-Ups/Venture Capital